QoS Driven Online Multicast Routing Algorithm - Manoharan, R.; Thambidurai, P.; Pradhiba, S. (Intelligent Information Technology, 2004)
Recent work on multicast routing algorithms in the Internet has introduced new notions of building online multicast tree without a priori knowledge of the future requests. Most of the online multicast routing algorithms aimed to satisfy more number of requests by preserving bandwidth on frequently used links and generate long-hop multicast trees by compromising the hop length. In this paper, we propose an online multicast routing algorithm, wherein rerouting of multicast session is incorporated instead of preserving bandwidth on frequently used links in order to satisfy more number of requests. This enables individual request to have different treatments based on their delay tolerance subject to policy restrictions. Our work focuses on classifying the requests into three classes namely Class-I, Class-II and Class-III and providing the maximum, the best possible and if possible service level in terms of bandwidth and end-to-end delay bound to efficiently utilize the network resources and accepting more user requests. Extensive simulations show that our algorithm provides service level guarantee to the three classes of requests, out performs the existing algorithms in terms of call acceptance ratio and improves the resource utilization.